Repeated sprint ability in young soccer players at different game stages - Meckel, Y.; Einy, A.; Gottlieb, R.; Eliakim, A. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to determine the repeated sprint ability (RSA) of young (16.9 ± 0.5 years) soccer players at different game stages. Players performed repeated sprint test (RST) (12 × 20 m) after warm-up before a game, at half-time, and after a full soccer game, each on a different day, in a random order. The ideal (fastest) sprint time (IS) and total (accumulative) sprint time (TS) were significantly slower at the end of the game compared with those after the warm-up before the game (p < 0.01 for each). Differences between IS and TS after the warm-up before the game and at half-time, and between half-time and end of the game, were not statistically significant. There was no significant difference in the performance decrement during the RST after warm-up before the game, at half-time, or the end of the game. Significant negative correlation was found between predicted VO2 and the difference between TS after the warm-up before the game and the end of the game (r = -0.52), but not between predicted VO2 and the difference in any of the RST performance indices between warm-up before the game and half-time, or between half-time and the end of the game. The findings indicate a significant RSA reduction only at the end but not at the half-time of a soccer game. The results also suggest that the contribution of the aerobic system to soccer intensity maintenance is crucial, mainly during the final stages of the game.